2014
DOI: 10.1016/j.virol.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor 1 and its role in viral carcinogenesis

Abstract: The advent of modern molecular biology has allowed for the discovery of several mechanisms by which oncoviruses promote carcinogenesis. Remarkably, nearly all human oncogenic viruses increase levels of the transcription factor hypoxia-inducible factor 1 (HIF-1). In this review, we highlight HIF-1׳s significance in viral oncogenesis, while providing an in-depth analysis of its activation mechanisms by the following oncoviruses: human papillomaviruses (HPVs), hepatitis B/C viruses (HBV/HCVs), Epstein-Barr virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 169 publications
0
79
0
5
Order By: Relevance
“…In recent studies, the role of HIF-1α in tumorigenesis has gradually been determined (13)(14)(15). The expression levels of HIF-1α were demonstrated to be significantly increased in multiple types of human cancer (12,13,16).…”
Section: Instructionmentioning
confidence: 99%
“…In recent studies, the role of HIF-1α in tumorigenesis has gradually been determined (13)(14)(15). The expression levels of HIF-1α were demonstrated to be significantly increased in multiple types of human cancer (12,13,16).…”
Section: Instructionmentioning
confidence: 99%
“…Recent studies have shown that a subunit of HIF-1α gene is overexpressed in breast cancer [15]. The C1772T polymorphisms are the most widely studied, which induce proline-to-serine amino acid substitutions and associated with increased HIF-1α expression in breast cancer [16]. The C>T change at 1772 causes the increase of Pro/Ser variation at codon 582 [17].…”
Section: Discussionmentioning
confidence: 99%
“…The beta subunit is an oxygen-independent constitutive protein located in the cell nucleus [22]. The process of alpha subunit degradation is initiated by posttranslational hydroxylation of amino acids proline 402 and proline 564 [23][24][25]. Because of hydroxylation, the alpha subunit of HIF protein is recognized by the von Hippel-Lindau protein (pVHL), a fragment of the ubiquitin ligase complex.…”
Section: Hif-1 Proteinmentioning
confidence: 99%